ANALISIS KEBUTUHAN E-MODUL MULTIMODAL BERKEARIFAN LOKAL MADURA UNTUK MENULIS TEKS CERPEN - Farahiba, Ayyu Subhi; Puspitasari, Mega (Universitas Andalas, 2024)
Multimodal e-modules develop students' abilities in understanding a variety of multimodal texts which encourage intellectual quality and broader learning experiences. Multimodal-based learning can be integrated with local wisdom as an effort to preserve cultural values. The aim of the research is to determine the need for a multimodal e-module based on Madurese local wisdom for writing short story texts. This research is aqualitative descriptive research oriented towards the development of a product. The data collection technique was carried out through a questionnaire distributed to Indonesian language teachers and also to students at two high schools in Pamekasan Regency via Google Forms. Data were analyzed using descriptive analysis and the percentage of the total number of answers given was divided by the total number of respondents multiplied by 100%. The results of this research show that learning to write short story texts has never been carried out using e-modules, the use of multimodal teaching materials has never been done, and the short story texts presented in learning have not been based on local Madurese wisdom. Based on these results, it can be concluded that the development of a multimodal e-module based on local Madurese wisdom is really needed by students so it needs to be developed to support the short story writing skills of class XI high school students.Â